2016
DOI: 10.1177/0267658315620265
|View full text |Cite
|
Sign up to set email alerts
|

L1 frequency in foreign language acquisition: Recurrent word combinations in French and Spanish EFL learner writing

Abstract: This study investigated French and Spanish EFL (English as a foreign language) learners’ preferred use of three-word lexical bundles with discourse or stance-oriented function with a view to exploring the role of first language (L1) frequency effects in foreign language acquisition. Word combinations were extracted from learner performance data (i.e. argumentative essays), and the frequency of their translation equivalent forms was analysed on the basis of French and Spanish L1 corpora. Strong and positive mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 47 publications
1
18
0
1
Order By: Relevance
“…Simply put, L2 learners may rely on the distributional and statistical regularities in their L1 when first learning an L2, and this may influence the frequency of the words they produce. This finding mirrors that of a recent study by Paquot (2017) in which she reported parallel frequencies between discourse-oriented lexical bundles in L2 learners’ first and second languages leading her to conclude that L1 frequency has an impact on L2 frequency.…”
Section: Discussionsupporting
confidence: 87%
“…Simply put, L2 learners may rely on the distributional and statistical regularities in their L1 when first learning an L2, and this may influence the frequency of the words they produce. This finding mirrors that of a recent study by Paquot (2017) in which she reported parallel frequencies between discourse-oriented lexical bundles in L2 learners’ first and second languages leading her to conclude that L1 frequency has an impact on L2 frequency.…”
Section: Discussionsupporting
confidence: 87%
“…Knowledge of FS has been shown to benefit language processing in both native speakers and L2 learners (e.g., Siyanova-Chanturia & Martinez, 2015; Underwood, Schmitt, & Galpin, 2004). The use of FS has also been found to be a key predictor of L2 writing and speaking proficiency (Boers et al, 2014; Crossley, Salsbury, & McNamara, 2015; Paquot, 2017). As such, knowledge of FS is considered to play a crucial role in attaining nativelike L2 proficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Following the Zipfian principles referred to in Section 2, a combination of three wellestablished general EAP vocabulary lists was used to ensure appropriate coverage was given to words with the potential to improve the collocation repertoire of EAP users: the Academic Keyword List (Paquot 2010), the Academic Collocations List (Ackermann & Chen 2013) and a subset of the Academic Vocabulary List (Gardner & Davies 2014) identified by Durrant (2016) as being particularly relevant to novice writers. Since the three lists are based on different corpora and different extraction methods, combining them allows us to prioritize what they have in common.…”
Section: Lexicographic Datamentioning
confidence: 99%
“…We nevertheless acknowledge that EAP users of different first language backgrounds may experience diverse problems regarding the use of collocations. It is well-documented that the ways in which second language writers combine words can be negatively impacted by their first languages (Nesselhauf 2005; Laufer & Waldman 2011; Peters 2016; Paquot 2017). By the same token, as shown in Frankenberg-Garcia (2018), less experienced native English EAP users tend to employ general language words and collocations which may sound out of place in formal academic writing.…”
Section: The Collocaid Projectmentioning
confidence: 99%